Da’wah of Digital Era Applicative Study: Qs. An-Nahl: 125 on Millennial Generation - Muhammad Raihan Nasution (Budapest International Research and Critics University, 2019)
In this digital era, young people are very vulnerable to negative things, therefore Islam as a religion which is rahmatan lil alamin, must take appropriate and fast actions to save young generations of Islam from getting lost in the darkness of cyberspace life. This article is prepared with a library research approach by conducting a literature review and collecting data from various sources and subsequently, the data is analyzed descriptively by presenting facts or findings which are then theoretically reviewed. Therefore da’wah of digital era really must use the media, especially new media. The development of communication technology has changed the way people communicate and interact. Nowadays, almost everyone uses the internet to send, search, and read information. Therefore, the Qur’an Surah An-Nahl: 125 offering da'wah methods of digital era have to be able to attract sympathetic Millennials, presenting representative, interactive and innovative da'wah methods through social media is the best way to save the young generations of Islam in the future.